(untitled) (Research, Society and Development, 2020)
Brazil is one of the main producers of reforested wood in the world, occupying the ninth position in the ranking of forest stand areas. The objective of this research is to analyze the situation of the planted forest market in state of Pará, as a way to understand its relative participation in the national context, characterizing the main cultivated species, the producing municipalities, the companies with performance and expertise in the branch and highlight the challenges and opportunities in the sector. The data used were obtained from the Brazilian Institute of Geography and Statistics (IBGE) for the period from 2013 to 2019. The variables analyzed were production in cubic meters (m³), production value in reais (R), harvested area in hectares (ha), price in reais per cubic meter (R.m-³). It was verified that the state of Pará participates with 1.9% of the national production, occupying the 11th position in the Brazilian production ranking. The growth of production in Pará comes since 2015, mainly from the cultivation of eucalyptus. The use of techniques in precision forest management, modern planting projects in the state, contribute to greater production of planted wood. Forest stands are renewable alternatives with great economic potential, mainly to occupy already altered areas, however, it is remarkable that there are still few studies related to the commercial planting of other species.